UNITED NATIONS RESOLUTION ON SREBRENICA GENOCIDE,SOLUTION OR DISSOLUTION OF BOSNIA AND HERZEGOVINA? (Security Dialogues, 2024)
The General Assembly of the United Nations adopts Resolution on SrebrenicaGenocide on 23 May 2024, designating 11 July as the „International Day of Reflection andCommemoration of the 1995 Genocide in Srebrenica“. The Resolution on Srebrenica Genocidewas adopted by a vote of 84 in favour to 19 against, with 68 abstentions. One of the objectivesof adopting the Resolution on Srebrenica Genocide is to condemne any denial of Srebrenicagenocide and actions that glorify those convicted of war crimes, crimes against humanityand genocide by international courts. The adoption of the Resolution on Srebrenica Genocideresonates in the region of the Western Balkans, but also far beyond its borders. Part ofthe statements that preceded the adoption of the Resolution on Srebrenica Genocide andthat appeared in public after its adoption may exacerbate tensions, and even existenceof Bosnia and Herzegovina. Aim of this paper is to analyze the statements and narrativesrelate to Resolution on Srebrenica Genocide and put it in the context of the current politicaland security situation in Bosnia and Herzegovina. Does the adoption of the Resolution onSrebrenica Genocide lead to further reconciliation of the people in Bosnia and Herzegovina?Will there be a review of the conflicts of the last century in Western Balkan region after this?